Effects of MTHFD1 overexpression on lipid synthesis in the oleaginous fungus : Mortierella alpina - Wang, Qizai (fi=Turun yliopisto|en=University of Turku|, 2018)
Mortierella alpina (M. alpina) is a filamentous fungus with a high polyunsaturated fatty acid content, but its sources of NADPH needed for lipid synthesis are not been studied completely. The binary vector pBIG2-ura5s-MTHFD1 was constructed for the transformation of the methylenetetrahydrofolate dehydrogenase (MTHFD1) gene into M. alpina (uracil auxotrophic) strain by Agrobacterium tumefaciens-mediated transformation (ATMT). PCR analysis identified the presence of the MTHFD1 overexpression cassette in the genome, and qPCR analysis showed that the transcript levels of the MTHFD1 gene in MTHFD1 overexpression strain (MA-MTHFD1) were significantly increased compared to controls. The results showed that MTHFD1 overexpression influenced lipid synthesis significantly. Compared to prototrophic M. alpina, the total fatty acid (TFA) level increased by about 40.1% and NADPH level simultaneously increased by 26.5% in MA-MTHFD1. Moreover, two key enzymes in NADPH synthesis were up-regulated: malate dehydrogenase and isocitrate dehydrogenase were increased by 38.4% and 43.3%, respectively. Based on the results, MTHFD1 plays an important role in NADPH generation during lipid synthesis in M. alpina. This study lays a foundation for uncovering mechanism of lipogenesis in M. alpina.